If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -8m = 0 Solving 12 + -8m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -8m = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -8m = 0 + -12 -8m = 0 + -12 Combine like terms: 0 + -12 = -12 -8m = -12 Divide each side by '-8'. m = 1.5 Simplifying m = 1.5
| 3ax+2y-5=0 | | 6x-4=-40+2x | | X^3-3x-10/3 | | (7/10)-(1/5x) | | (7/75)*(7/75) | | A*2-12=26.44 | | x=145-2/3x | | 3x/7=33 | | -2x(4y)+8=4y | | 2s/3-s/6=2 | | 35000=44x+52000 | | 1400=44x+52000 | | C(35000)=44x+52000 | | C(1400)=44x+52000 | | 12x+3x-(-10)=0 | | 7y+2=-5y-10 | | C(x)=44x+52000 | | 3n-5+2n=8+n | | X^2+6x+y^2=16 | | 12*12=6*x | | (9*^2)^1/2 | | 3y*6y= | | 1.23=2t-5t^2 | | x=2t-5t^2 | | 180-(8x+20)+40+(3x+10)=180 | | 2p^2-9p-143=0 | | 2y=6y+7 | | (3+y)(5y-7)= | | 5/7g=5/8 | | (5y^2)+(3x^2)=125 | | -5x^2+5x=-2 | | (5x^2)+(3y^2)=125 |